2015
DOI: 10.1080/19475705.2015.1084541
|View full text |Cite
|
Sign up to set email alerts
|

Mapping regional forest fire probability using artificial neural network model in a Mediterranean forest ecosystem

Abstract: Forest fires are one of the most important factors in environmental risk assessment and it is the main cause of forest destruction in the Mediterranean region. Forestlands have a number of known benefits such as decreasing soil erosion, containing wild life habitats, etc. Additionally, forests are also important player in carbon cycle and decreasing the climate change impacts. This paper discusses forest fire probability mapping of a Mediterranean forestland using a multiple data assessment technique. An artif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
90
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(93 citation statements)
references
References 19 publications
0
90
0
3
Order By: Relevance
“…These often involve the implementation of physically-based models integrated into a Geographic Information System (GIS), relying on expert knowledge or including statistical analyses and modeling to assess the importance of the predisposing factors [15][16][17][18][19][20][21][22][23][24]. Lately, the comparison of deterministic physically-/statistically-based and stochastic approaches highlights the benefit of using data driven methods [25][26][27][28][29][30][31][32][33] that are able to extract knowledge directly from data. Machine learning has proven to be a mature and reliable tool in quantitative wildfire-related studies, as for the estimation of standing crop and fuel moisture content, often outperforming standard statistical approaches [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…These often involve the implementation of physically-based models integrated into a Geographic Information System (GIS), relying on expert knowledge or including statistical analyses and modeling to assess the importance of the predisposing factors [15][16][17][18][19][20][21][22][23][24]. Lately, the comparison of deterministic physically-/statistically-based and stochastic approaches highlights the benefit of using data driven methods [25][26][27][28][29][30][31][32][33] that are able to extract knowledge directly from data. Machine learning has proven to be a mature and reliable tool in quantitative wildfire-related studies, as for the estimation of standing crop and fuel moisture content, often outperforming standard statistical approaches [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…The integration of alternative geocomputational techniques for fire risk mapping is a potential topic for future research. Neural networks, classification and regression trees (CARTs), fuzzy modeling, and evolutionary algorithms may provide new methods for mapping fire risk [198][199][200].…”
Section: Fire Risk Assessment and Mappingmentioning
confidence: 99%
“…However, a number of studies have shown that machine learning algorithms can provide improved accuracy over statistical methods and are more likely to reduce the spatial autocorrelation effect (Bisquert et al 2012;Oliveira et al 2012;Massada et al 2013). Machine learning algorithms previously used for forest fires probability risk mapping include maximum entropy (MaxEnt) (Parisien & Moritz 2009;Parisien et al 2012), random forest (RF) (Oliveira et al 2012;Arpaci et al 2014), artificial neural networks (ANN) (Bisquert et al 2012;Satir et al 2015), and support vector machines (SVM) (Sakr et al 2010). Of these algorithms, RF and MaxEnt have shown improved accuracy over ANN and SVM for spatial predictions (Oliveira et al 2012;Massada et al 2013;Olaya-Mar ın et al 2013;Rodrigues & de la Riva 2014).…”
Section: Introductionmentioning
confidence: 99%